Label Nutri-Level pada Kemasan Pangan sebagai Instrumen Kebijakan Kesehatan dalam Mendorong Perilaku Konsumsi Sehat Masyarakat - Fariz Kahendra; Paramita Boni Lestari; Ahmad Daffa Aushof; Apriliana Nabila; Tania Gunawan (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2026)
Non-communicable diseases remain a major public health challenge in Indonesia and are closely associated with the increasing consumption of processed foods high in sugar, salt, and fat. The implementation of the Nutri-Level Label on food packaging has been introduced as a public health policy to assist consumers in making healthier food choices. This community service program aimed to improve public knowledge and skills in understanding and utilizing the Nutri-Level Label as a basis for selecting healthier food products. An educational-participatory approach was employed through health education sessions and hands-on demonstrations on how to interpret Nutri-Level Labels displayed on food packaging. The program was conducted in June 2026 at the Sawah Besar District Sports Hall and involved 48 community participants. Participants' knowledge was assessed using a 10-item pre-test and post-test questionnaire covering the concept, function, label categories, and practical application of the Nutri-Level Label. The findings demonstrated an increase in the mean knowledge score from 61.5 before the intervention to 87.8 after the intervention. The proportion of participants with good knowledge increased from 31.3% to 85.4%, while those with poor knowledge decreased from 27.0% to 0%. Participants also showed improved ability to identify Nutri-Level categories and compare food products based on their nutritional quality. These findings indicate that educational interventions combined with practical demonstrations effectively enhance nutrition literacy and support the implementation of the Nutri-Level Label policy to promote healthier dietary behaviors.